2013
DOI: 10.1261/rna.042507.113
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific gene silencing monitored in circulating RNA

Abstract: Pharmacologic target gene modulation is the primary objective for RNA antagonist strategies and gene therapy. Here we show that mRNAs encoding tissue-specific gene transcripts can be detected in biological fluids and that RNAi-mediated target gene silencing in the liver and brain results in quantitative reductions in serum and cerebrospinal fluid mRNA levels, respectively. Further, administration of an anti-miRNA oligonucleotide resulted in decreased levels of the miRNA in circulation. Moreover, ectopic expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…To determine whether baseline hepatic ALAS1 mRNA expression could be detected in biological fluids, filtered serum, and urine from naive Sprague Dawley (SD) rats ( n = 3) were subjected to high-speed centrifugation, and total RNA was isolated from the resulting pellets as previously described. 35 Total RNA was extracted from livers harvested from the same animals. As shown in Figure 1a , mRNA presumably corresponding to the liver expressed ALAS1 could be detected in both the urine and serum by reverse-transcription quantitative PCR (RT-qPCR).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether baseline hepatic ALAS1 mRNA expression could be detected in biological fluids, filtered serum, and urine from naive Sprague Dawley (SD) rats ( n = 3) were subjected to high-speed centrifugation, and total RNA was isolated from the resulting pellets as previously described. 35 Total RNA was extracted from livers harvested from the same animals. As shown in Figure 1a , mRNA presumably corresponding to the liver expressed ALAS1 could be detected in both the urine and serum by reverse-transcription quantitative PCR (RT-qPCR).…”
Section: Resultsmentioning
confidence: 99%
“… 34 We have previously demonstrated the ability to detect mRNAs encoding tissue-specific gene transcripts, as well as their RNA-mediated reduction with siRNA administration in vivo , in biological fluids including serum and cerebrospinal fluid using a circulating extracellular RNA detection (cERD) method. 35 In an effort to extend this approach to monitor ALAS1 reduction with ALN-AS1 treatment, we developed a target-specific, cERD method to quantify hepatic ALAS1 mRNA levels using serum, and further optimized this method to use urine. We demonstrate herein a striking correlation between serum, urine, and liver ALAS1 transcript levels across a number of preclinical species including mice, rats, and non-human primates (NHP) following subcutaneous dosing with a GalNAc-siRNA conjugate targeting ALAS1 (ALN-AS1).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Alzheimer’s disease, miRNAs that are associated with neuropathological changes in post-mortem brain tissue have been detected in blood sera of subjects meeting ante-mortem criteria for the disease, albeit at lower basal levels [ 12 ]. The potential importance of such findings gains further support from a recent study that demonstrated serum mRNA levels could be directly regulated by brain-specific administration of RNAi [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DNA probe qPCR assay was used to determine the EBV copy number. Primers ( BamH I W F: 5′- CCCAACACTCCACCACACC -3′, R: 5′- TCTTAGGAGGCTGTCCGAGG -3′ [ 16 ], BALF5 F: 5′- CTGACAAGGAGTACCTGCGT -3′, R: 5′- GAATGACGGCGCATTTCTCG -3′ [ 11 ], DSR F: 5′- ATGTAAATAAAACCGTGACAGCTCA -3′, R: 5′- TTACCCAACGGGAAGCATATG -3′ [ 12 ], glyceraldehyde 3-phosphate dehydrogenase (GAPDH) gene F: 5′- TGTGCTCCCACTCCTGATTTC -3′, R: 5′- CCTAGTCCCAGGGCTTTGATT -3′ [ 17 ], and eGFP gene F: 5′- GACAACCACTACCTGAGCAC -3′, R: 5′- C AGGACCATGTGATCGCG -3′ [ 18 ]), and double-quenched fluorescent DNA probes ( Bam H I W: 5′- FAM/CACACACTA/ZEN/CACACACCCACCCGTCTC /IBFQ -3′, BALF5: 5′- FAM/CGGTCACAA /ZEN/TCTCCACGCTG/IBFQ -3′, DSR: 5′- FAM/CGAATTAGG/ZEN/CTTAGTAAAATGGTCC/ IBFQ -3′, GAPDH: 5′- FAM/CGGTCACAA/ZEN/TCTC CACGC/IBFQ -3′, eGFP: 5′- FAM/CCTGAGCAA/ZEN/GACCCCAACGAGAA/IBFQ -3′) were obtained from Integrated DNA Technologies (IDT, Coralville, IA, USA). The qPCR was performed in a 10 µL reaction volume containing 1 µL of gDNA template, 1 µL of 10 µM primers, 5 µL of 2X SSO Advanced Universal Probes Supermix (Bio-Rad, Hercules, CA, USA), and 1 µL of 5 µM DNA probe.…”
Section: Methodsmentioning
confidence: 99%
“…CCTAGTCCCAGGGCTTTGATT -3[17], and eGFP gene F: 5 -GACAACCACTACCTGAGCAC -3 , R: 5 -C AGGACCATGTGATCGCG -3[18]), and double-quenched fluorescent DNA probes (BamH I W: 5 -FAM/CACACACTA/ZEN/CACACACCCACCCGTCTC /IBFQ -3 , BALF5: 5 -FAM/CGGTCACAA /ZEN/TCTCCACGCTG/IBFQ -3 , DSR: 5 -FAM/CGAATTAGG/ZEN/CTTAGTAAAATGGTCC/ IBFQ -3 , GAPDH: 5 -FAM/CGGTCACAA/ZEN/TCTC CACGC/IBFQ -3 , eGFP: 5 -FAM/CCTGAGCAA/ZEN/GACCCCAACGAGAA/IBFQ -3 ) were obtained from Integrated DNA Technologies (IDT, Coralville, IA, USA). The qPCR was performed in a 10 µL reaction volume containing 1 µL of gDNA template, 1 µL of 10 µM primers, 5 µL of 2X SSO Advanced Universal Probes Supermix (Bio-Rad, Hercules, CA, USA), and 1 µL of 5 µM DNA probe.…”
mentioning
confidence: 99%